Business Strategy of Lily Catering in PT. Wilmar Cahaya Mandiri Cafeteria - Kurniasari, Fita; Saphiranti, Dona (The Indonesian Journal of Business Administration, 2016)
Abstract - Lily catering is a catering service provider in Kota Pontianak. In Desember 2015 Lily catering was open a cafeteria located in PT. WILMAR Cahaya Indonesia Factory. In this cafeteria Lily catering provide food for PT. WILMAR Cahaya Indonesiaâ€™s employees. However the sales in the cafeteria do not as expected. Lily catering is facing difficulties to reach the market in PT. WILMAR Cahaya Indonesia. The exchange eating coupon in second month is low, because there is some of competitor that offers the same product as Lily catering. They are earlier competitor in the area. To find out the root cause of Lily catering cafeteria business issues, Lily catering conduct analysis from external factors and internal factors. The method used for external analysis was Consumer Survey and Porter's Five Forces. For the internal analysis we used Segmentation, Targeting and Positioning (STP) analysis and Marketing-Mix 7P analysis. Based on those analyses, we found that the marketing mix analysis not match with the market, it cause Lily catering enable to reach the intended sales. The strategy that the Lily catering does is by proposed new marketing mix. The action plan were made so that Lily catering can start implement the new strategy as soon as possible to reach the market and grow.Â Keyword: Culinary business, cafeteria, business strategy